PENGARUH JUMLAH KUNJUNGAN WISATAWAN TERHADAP PENERIMAAN RETRIBUSI TEMPAT REKREASI DAN OLAHRAGA PADA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KEBUMEN TAHUN 2011-2014 - Wenny Marlini; Bahrudin Yusuf (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2018)
The number of tourist visits consists of adults and children, the amount will have an impact on tourism object and sport retribution. This research aimed to determine the effect of the number of tourist visit to income of tourism object and sport retribution at departement tourism and culture district Kebumen year 2011-2014. The research methods used by the writer weredescriptive and quantitativ methods. This study used a simple linear regression. Results of this analysis showed regression equation Y=-281.785.862,671+4.757,518X means that each additional 1 visitor would improve tourism object and sport retribution RP 4.750,00. Significance test result the number of tourist visit to income of tourism object and sport retributionat departement tourism and culture district Kebumen, was t of (4,678) was greater than the table t of (4,303)means that H0 was rejected and H1 was accepted. Results of this study could be concluded that a significant difference between the number of tourist visits towards tourism object and sport retribution. Keywords : The Number Of Tourist Visits, Tourism Object and Sport Retribution